A Rare Case of Pre-Existing Deep Venous Thrombosis in the Peroneal Vein of a Free Osteocutaneous Fibula Flap - Hayashi, Satoshi; Kawamura, Kenji; Maegawa, Naoki; Nakanishi, Akito; Mizutani, Yasushi; Okuda, Akinori; Kurata, Shinpei; Shimizu, Takamasa; Kira, Tsutomu; Omokawa, Shohei; Tanaka, Yasuhito (Journal of Reconstructive Microsurgery Open, 2018)
Background Deep venous thrombosis (DVT) of the lower leg is a widespread medical problem and is associated with hypercoagulable states. Although spontaneous thrombosis of the peroneal vein of a fibula flap is theoretically possible, few cases of asymptomatic DVT of the peroneal vein encountered during fibula flap harvest have been reported.Case Report A 45-year-old man presented with segmental bone defects of the tibia resulting from a fall. Treatment with a free vascularized osteocutaneous fibula flap from the contralateral lower leg was scheduled. Intraoperatively, diffuse thrombi were found in the peroneal venous system. After removal of thrombi, the fibula was grafted with anastomosis of the peroneal vessels to the recipient posterior tibial vessels. The skin paddle of the flap became congested after surgery; exsanguination of the skin paddle was performed with multiple skin incisions to relieve congestion. Despite treatment, the skin paddle became partially necrotic and additional skin grafting was performed. Bone union of the grafted fibula was achieved 5 months after initial surgery.Conclusions To the best of our knowledge, only six cases of pre-existing DVT in the peroneal vein of a free osteocutaneous fibula flap have been reported. In three of these cases, the fibula flap was successfully grafted. Although successful free osteocutaneous fibula flap surgery might be possible in patients with peroneal venous thrombosis, careful preoperative evaluation is recommended for high-risk patients.
Keywords: osteocutaneous fibula flap; deep venous thrombosis; peroneal vein